Influence of Monomer Concentration on the Morphologies and Electrochemical Properties of PEDOT, PANI, and PPy Prepared from Aqueous Solution. (24th October 2016) - Kulandaivalu, Shalini; Zainal, Zulkarnain; Sulaiman, Yusran
Abstract : Poly(3, 4-ethylenedioxyhiophene) (PEDOT), polyaniline (PANI), and polypyrrole (PPy) were prepared on indium tin oxide (ITO) substrate via potentiostatic from aqueous solutions containing monomer and lithium perchlorate. The concentration of monomers was varied between 1 and 10 mM. The effects of monomer concentration on the polymers formation were investigated and compared by using Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, scanning electron microscopy (SEM), cyclic voltammetry (CV), and electrochemical impedance spectroscopy (EIS) measurements. FTIR and Raman spectra showed no changes in the peaks upon the increment of the concentration. Based on the SEM images, the increment in monomer concentration gives significant effect on morphologies and eventually affects the electrochemical properties. PEDOT electrodeposited from 10 mM solution showed excellent electrochemical properties with the highest specific capacitance value of 12.8 mF/cm 2 .